O adicional de penosidade e a de efetivação do direito humano fundamental ao meio ambiente do trabalho saudável - Ferreira, Magdalena Araujo Pereira (2023)
The present work aims to analyze the possibility of realizing the fundamental human right to a healthy work environment in the face of the lack of regulation of the additional hardship, provided for in art. 7, XXIII of the Brazilian Federal Constitution. To this end, general aspects of the environment and the legal nature of the work environment were analyzed, considering it as a fundamental human right and classifying it as a diffuse right of the 3rd dimension. The structuring principles of the work environment were addressed, with emphasis on the principles of human dignity, prevention and precaution for the environment, the polluter pays, sustainable development, as well as the apparent antinomy between the norms that determine the reduction of the risks inherent to work (art.7, XXII of the CRFB) with the possibility of remuneration for painful, unhealthy or dangerous work provided for constitutionally (art.7, XXIII, of the CRFB) and the question of the existence, validity and effectiveness of the legal norms and the horizontal effectiveness of fundamental rights. In addition, the norms for the protection of workers' health and safety were observed at the international level, with an analysis of the main ILO conventions (155 and 161), constitutional and infraconstitutional norms, which aim to eliminate risk and ensure a safe and secure work environment. In conclusion to the proposed problem, an analysis was presented on the lack of regulation of the additional hardship and the ways of realizing the fundamental human right to a healthy work environment. In conjunction with the study, the appreciation of the forms of perverse work (thus considered unhealthy, dangerous or painful activities), the projects to regulate the additional burden of hardship, the performance of the Judiciary and examples of painful activities, such as working in the sugar cane cutting, bus drivers and collectors and the public service of urban public cleaning. Thus, research on the subject is significant so that, under the norms and principles that govern environmental law, it is possible to outline paths that can guarantee a healthy quality of life for workers, regardless of the existence of ordinary laws regulating the aforementioned additional.